What Drives Customers to Buy? The Dominant Role of Menu Variation at Cafe Rumakadua, Indonesia - Zandy Pratama Zain; Irfandi Buamonabot; Eka Satirianisa Mappe; Safri Panigoro; Ruland Willy Jack Sumampouw (SAN Scientific, 2026)
This study aims to analyze the influence of social media marketing and menu variety on purchase decisions, with price as a mediating variable, at Cafe Rumakadua. The rapid growth of the culinary MSME industry in Indonesia has intensified competition, prompting cafes to optimize their digital marketing strategies and innovate their products simultaneously. This research employed a quantitative approach, using survey data collected from 200 Cafe Rumakadua customers via purposive sampling. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that menu variety has a positive, significant effect on both price perception and purchase decisions, demonstrating that diverse menu offerings strengthen consumer value perception and encourage purchase behavior. Social media marketing significantly influences price perception but does not directly affect purchase decisions. Furthermore, price does not significantly influence purchase decisions and fails to mediate the relationship between social media marketing, menu variation, and purchase decisions. These results suggest that consumers are more attracted to product diversity and experiential value than to price alone. This study contributes to the digital marketing and consumer behavior literature by emphasizing the strategic importance of menu innovation in shaping customer purchasing decisions in the culinary MSME sector.